The Perception of Bantaragung Village Community Toward the Factors Affecting the Development of a Tourism Village Through Sustainable Livelihood Approach - Dwita Apriani; Kurniawan Saefullah; Cupian (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2023)
Bantaragung Village, Sindangwangi District, Majalengka Regency, is a village that is currently growing rapidly and has been named as a tourism village and has earned a label as a potential tourism village from the Minister of Tourism and Creative Economy (Menparekraf). However, in its development, its popularity as a tourism village has not been matched by the speed of increasing management capacity and other supporting factors, so it has not been optimal as a commercial tourism destination. The purpose of this study is to identify the factors affecting the development of a tourism village in Bantaragung Village based on the perceptions of the village community using the Sustainable livelihood approach. The sampling method used non-probability sampling with a purposive sampling technique on 30 respondents. The data analysis employed a quantitative descriptive method with five livelihood asset variable objects: natural, human, financial, social, and village infrastructure. The findings of the study show that the livelihood framework assets that primarily affect the development of Tourism Villages in Bantaragung are natural resources, followed by financial, social, human resources, and village infrastructure.